Capital Flows and the International Credit Channel - Yusuf Soner Baskaya; Julian Di Giovanni; Sebnem Kalemli-Ozcan; José-Luis Peydró; Mehmet Fatih Ulu (Journal of International Economics, 2017)
We examine the role of the international credit channel in Turkey over 2005–2013. We show that larger, more capitalized banks with higher non-core liabilities increase credit supply when capital inflows are higher. This result is stronger for domestic banks relative to foreign banks and survives during the crisis period of post-2008, when foreign banks in general stop lending in emerging markets and retreat to their home countries. By decomposing capital inflows into bank and non-bank flows, we show the importance of domestic banks' external borrowing for domestic credit growth.
Keywords: E0; F0; F1; 330; capital flows; bank-lending channel; bank heterogeneity